Psychometric characterization of an instrument of organizational climate in the Colombian university education sector - Castillo, Ledy (Editorial Bonaventuriana, 2018)
The aim of this study was to characterize psychometrically an instrument for measuring organizational climate for higher education institutions. The methodology refers us to a cross-sectional study, we obtained a total sample of 662 participants. Obtained a Cronbach alpha 0 = 0.91, which means a very good internal consistency of the test. In the inter item correlation analysis, which refers to another element of internal consistency, there were significant positive correlations (p = 0.01). Observed in the factor analysis, which measures the final test for 51.3% of the total variance explained in five factors. In general, it presents an instrument with adequate psychometric characteristics for measuring the organizational climate in higher education educations.